Sistem Pendanaan Proyek Perusahaan Jasa Konstruksi Berbasis Web - Hilyah Magdalena; Hadi Santoso; Litha Leonita (Faculty of Computer Science, University of Jember, 2021)
CV. Yusti Karya as a construction company realizes that the ability to manage project finances is an important requirement for smooth project management. CV.Yusti Karya often has to manage several projects simultaneously in remote locations. This condition makes it difficult for the finance staff in the office to manage project financial allocations and also makes it difficult for project managers in the field and must report the status of project expenditures to the office. This difficulty drives CV. YustiKarya improved the project's financial management system from using spreadsheets to a web-based information system. Web-based information system will be developed using object-oriented methods. The object- oriented system development method was chosen because of its modular development capabilities and adapts to system requirements. The development of this system aims to enable Person in Charge (PIC) projects in the field to submit expenditures and can be immediately approved by the financial staff in charge. Online project finance management between project PICs and finance staff helps harmonize financial management. The Director can monitor the flow of the latest project finance developments online.